Risk Factors Associated with the Incidence of Diarrhea in Toddlers in the Working Area of Putri Ayu Health Center, Jambi City in 2025 - Rahmalisa Safitri; Andy Amir; Fajrina Hidayati (CV. AFDIFAL MAJU BERKAH, 2025)
Diarrhea in toddlers is one of the main causes of death in children. The Putri Ayu Health Center area in Jambi City is the area with the highest prevalence of diarrhea cases in toddlers in Jambi City, which is (5.1%). This study aims to determine the relationship between clean water facilities, toilets, waste management, waste disposal, maternal employment status, and maternal education with the incidence of diarrhea in toddlers in the Putri Ayu Health Center area in Jambi City in 2025. This type of research is quantitative research with a cross-sectional study design. The population in this study were all mothers of toddlers in the working area of ​​Putri Ayu Health Center, Jambi City. The sample in this study was 70 mothers of toddlers. The sampling technique used proportional random sampling. Data collection used questionnaires and observations, univariate and bivariate data analysis used the chi-square test. The proportion of diarrhea incidence was 37.1%. There was a relationship between toilets (p = 0.036, PR = 2.118), waste management facilities (p = 0.043, PR = 3.556), waste disposal facilities (p = 0.028, PR = 3.849) with the incidence of diarrhea in toddlers. There was no relationship between clean water facilities, maternal employment status, and maternal education with the incidence of diarrhea. The related variables are toilet facilities, waste management facilities and waste disposal facilities. Therefore, it is recommended to maintain the environment, both toilets, waste management and waste disposal.